2016
DOI: 10.1111/cpr.12262
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐free microRNAs in blood and other body fluids, as cancer biomarkers

Abstract: The discovery of cell-free microRNAs (miRNAs) in serum, plasma and other body fluids has yielded an invaluable potential source of non-invasive biomarkers for cancer and other non-malignant diseases. miRNAs in the blood and other body fluids are highly stable in biological samples and are resistant to environmental conditions, such as freezing, thawing or enzymatic degradation, which makes them convenient as potential biomarkers. In addition, they are more easily sampled than tissue miRNAs. Altered levels of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 236 publications
(349 reference statements)
0
88
0
3
Order By: Relevance
“…miRNAs have been highlighted as potential circulating biomarkers and therapeutic targets for BC (17). Other markers such as ER, PR, and Her2/neu position would indicate ideal adjunct remedy situation (9). Several studies linked miR-155 to inflammation in cancer (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs have been highlighted as potential circulating biomarkers and therapeutic targets for BC (17). Other markers such as ER, PR, and Her2/neu position would indicate ideal adjunct remedy situation (9). Several studies linked miR-155 to inflammation in cancer (18).…”
Section: Discussionmentioning
confidence: 99%
“…The emerging evidence indicating that certain microRNAs (miRNAs) are extensively involved in BC progression has led to the search for good miRNA candidates for classifying tumors (8). Recently, it has been found that these miRNAs in serum proteins, lipoproteins, and proteins make connections called Argonaute-2 causing the miRNAs in serum safeguarded and protected from ribonucleases (9). In addition, closeby markets and protection by secreting substances such as objects are imported Apoptotic and exosomes in the blood serum and secretory vesicles containing miRNAs addition; it can act as carriers of messages between cells miR-155, a miRNA to be involved in lymphoma is also rising to possess a role in the progression of solid cancer (10).…”
Section: Introductionmentioning
confidence: 99%
“…EVs participate in cell–cell communication and can typically be classified based on their size (from 4 to 10 microns), intracellular origin, and density (Cocucci and Meldolesi, 2011; Raposo and Stoorvogel, 2013; Valadi et al ., 2007). EVs can be found in all different body fluids, such as blood, serum, plasma, saliva, urine, and pleural effusions (Fernandez‐Mercado et al ., 2015; Liu et al ., 2017a; Mitchell et al ., 2008; Ortiz‐Quintero, 2016; Weber et al ., 2010). In the last decade, several studies have shown that EVs are enriched for various proteins, such as cytokines, messenger RNAs, lipids, and noncoding RNAs, such as miRNAs and long noncoding RNAs (lncRNAs) (Colombo et al ., 2013; Valadi et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…To date, for each cancer type analyzed (and often stratified by stage), miRNA signatures have been identified that may be prognostic and/or predictive [41, 42]. Distinct miRNA panels of a primary and its metastases, in either clinical sets or preclinical models, have been reported [43].…”
Section: Mirnas In Neoplasiamentioning
confidence: 99%
“…These include the following: (1) passive leakage of miRNAs from damaged cells (apoptosis, necrosis, chronic inflammation, tissue injury, or normal cells with a short half-life, e.g., platelets [71, 72]); (2) secretion within encapsulated microvesicles, exosomes, or shedding vesicles [34, 73, 74]; and (3) secretion through association with complexes that are RNA binding, such as Argonaute 2 (Ago2) [72, 75], nucleophosmin (NPM1) [76], or high-density lipoprotein [77]. At present, there is no consensus regarding the precise biological mechanisms underlying miRNA secretion [41]. …”
Section: Mirnas In Bloodmentioning
confidence: 99%